2017
DOI: 10.1007/s11255-017-1667-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-adrenergic receptor subtypes in human normal and dilated ureter

Abstract: The downregulation of β-ARs after ureter dilation, particularly for β1-AR and β3-AR in the muscular layer, suggests a potential compensatory mechanism involving increased contraction of the ureter to push urine through the obstruction. Thus, β-ARs may be a potential target for treatment of ureter obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Moreover, Shen et al. recently reported, based on a human ureter immunochemistry analysis, that all β‐adrenergic receptor subtypes were expressed in the mucosa and muscular layers of the human ureter and that expression was downregulated in cases of ureter dilatation . They demonstrated that the use of highly selective β‐1 and β‐3 agonists acting on ureteric smooth muscle lesions might help reduce the symptoms of ureteric smooth muscle spasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Shen et al. recently reported, based on a human ureter immunochemistry analysis, that all β‐adrenergic receptor subtypes were expressed in the mucosa and muscular layers of the human ureter and that expression was downregulated in cases of ureter dilatation . They demonstrated that the use of highly selective β‐1 and β‐3 agonists acting on ureteric smooth muscle lesions might help reduce the symptoms of ureteric smooth muscle spasm.…”
Section: Discussionmentioning
confidence: 99%
“…Sigala et al [26] presented gene expression analysis in which a-1d adrenergic receptor mRNA was expressed in all portions of the ureter, especially in the distal ureter [26]; therefore, a-blockers have some degree of selectivity for the detrusor and the distal ureter, and have the potential to promote dilatation of the ureter and decrease pain. Moreover, Shen et al [27] recently reported, based on a human ureter immunochemistry analysis, that all b-adrenergic receptor subtypes were expressed in the mucosa and muscular layers of the human ureter and that expression was downregulated in cases of ureter dilatation [27]. They demonstrated that the use of highly selective b-1 and b-3 agonists acting on ureteric smooth muscle lesions might help reduce the symptoms of ureteric smooth muscle spasm.…”
Section: Discussionmentioning
confidence: 99%
“…β 3 -AR has been localized in kidneys [3] and in the lower urinary tract [81] including ureters [82], urethra [83], prostate [84], and bladder [85] where it appears to be the predominant subtype [86] although this idea was recently challenged in a wide transcriptomics analysis across several human tissues [80].…”
Section: β3-ar As Therapeutic Targetmentioning
confidence: 99%
“…β 3 -AR are also present in the lower urinary tract where they undergo pathophysiological changes in expression upon the initiation of lower urinary tract symptoms due to ureteral stenosis [82], chronic kidney disease, end stage renal disease, or certain carcinomas [100]. The β 3 -AR agonist mirabegron for the oral pharmacotherapy of patients affected by overactive bladder syndrome (OAB) is currently the most promising agent in over 30 years.…”
Section: β3-ar As Therapeutic Targetmentioning
confidence: 99%
“…Their results showed that β3-AR expression were decreased by 53.62% (p < 0.01) in the muscular layer of the lower segment of the dilated ureter, suggesting a possible physiological compensatory mechanism which results in an increased contraction of the ureter to propel urine through the obstructed lumen. 8 Hence, the potential role for mirabegron as a medical expulsive therapy arised. 9…”
Section: Expression Of β-Adrenergic Receptors In the Uretermentioning
confidence: 99%